Since, the terms are in an AP, therefore
(3n + 2) - (2n - 1) = (6n - 1) - (3n + 2)
⇒ n + 3 = 3n - 3
⇒ 2n = 6
⇒ n = 3
∴ n= 3, and hence the numbers are 5, 11, 17.
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Arithmetic Progression- Don't miss these Questions56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation